Polymeric gels for drug delivery - Deen, G. Roshan; Safar, Dora (Henry Stewart Talks, 2022)
Hydrogels, Types of hydrogels, Properties of Hydrogels, Stimuli-responsive hydrogels, Classification of hydrogels, Degree of swelling and types of water in swollen gels, Differential Scanning Calorimetry (DSC), Drug delivery systems, Supramolecular hydrogels, Quantum dot-DNA hybrid hydrogels, Hydrogel products, Routes of administration, Medical applications of hydrogels, Applications in cardiac tissue engineering